Decline or Transformation: Lao Modern Culture Under a Social Media Lens - WU, zhi (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study investigates the cultural implications of the significant increase in social media users in Laos, which has grown nearly forty-fold since 2011. Using digital ethnography conducted between 2011 and 2024 on platforms such as Facebook and YouTube, the research explores whether these digital shifts signify cultural decline or transformation. The analysis focuses on linguistic hybridity and the evolution of music as key indicators of cultural adaptation. Findings suggest that Lao culture is not in decline but is instead skillfully incorporating global influences while actively participating in digital spaces. This demonstrates a trajectory of cultural transformation. The study contributes to the field of digital anthropology by offering insights into how Lao culture negotiates its identity within an increasingly interconnected digital environment.